THE ENTREPRENEURIAL UNIVERSITY: WHY FOCUSING ON THE ORGANIZATION OF STUDENT LIFE? - Sidrat, Sawsen; Boujelbene, Younes (Journal of Business And Entrepreneurship, 2022)
To develop an entrepreneurial university, the organization of student life has become an increasingly relevant topic. The current paper aims to develop a model relating to the organization of student life. Therefore, the paper’s objective is specifically to analyze the importance of para-academic factors and the role that they can play in the development of an entrepreneurial university. To reach tis end, we conducted a quantitative study on 230 Tunisian students. The obtained results show that students’ previous professional experiences and associative life have a positive impact on the development of an entrepreneurial university. The originality of this research lies in the design of a model that attempts to explain how to structure student life in order to develop an entrepreneurial university. We are particularly interested in the image of the ‘dynamic student’ as the main driving force behind the development of an entrepreneurial university